Cognitive rehabilitation for memory deficits after stroke - das Nair, Roshan; Cogger, Heather; Worthington, Esme; Lincoln, Nadina (American Heart Association, 2017)
Memory problems are common after a stroke, leading to difficulties in everyday life. Memory rehabilitation aims to help retrain lost functions or to teach patients strategies to compensate for them. Although some studies have reported positive outcomes after memory rehabilitation, reviews have provided inconclusive evidence for effectiveness. This is an update of a Cochrane review first published in 2000 and subsequently updated in 2007